A controlled pilot intervention on community violence prevention, financial and social capital generation in Dar Es Salaam, Tanzania - Louis Jansen; Anne H. Outwater; Michael Lowery Wilson; Masunga K. Iseselo; Till Bärnighausen (BMC, 2022)
Abstract Background Community violence has been found to be highly prevalent in Dar es Salaam, Tanzania. Increasing socioeconomic inequality has been outlined as one of the main causes of community violence. This controlled pilot trial aimed at evaluating the impact of beekeeping and entrepreneurship training on community violence exposure, financial and social capital generation, and employment structure. Methods Poisson regression was used to compare pre- and post-intervention risk ratios for community violence exposure. Linear regression was used to depict change in weekly income and utu scores. Employment rate structures were determined pre- and post-intervention. Results This study reports that compared to the Control arm beekeeping and entrepreneurship training appears to have protected young men in Dar es Salaam from exposure to community violence (All = 0.62 (0.40-0.96), Beekeeping = 0.57 (0.30-1.08), Entrepreneurship = 0.62 (0.33-1.17)), while increasing financial (All = 23,145 (− 27,155 - 73,444), Beekeeping = 29,310 (− 26,079 - 84,698), Entrepreneurship = 82,334 (12,274 - 152,293)) and partially also social capital (All = − 0.24 (− 1.35-0.87), Beekeeping = 0.85 (− 0.26-1.96), Entrepreneurship = 0.30 (− 1.16-1.77)). Financial dependency across all arms was reduced from 29.1 to 2.2%. Conclusions Our study reports that beekeeping training and entrepreneurship seminars appear to have a protective effect against exposure to community violence among young men in Dar es Salaam, while partially also increasing financial and social capital, as well as reducing financial dependency. We recommend that these results should lay the foundation for an adequately powered randomized trial to confirm the study's efficacy. Trial registration retrospectively registered at ClinicalTrials.gov (Identifier: NCT04602416; October 26, 2020).